The utility of a model-based cost-effectiveness analysis of degarelix versus leuprolide in the therapy of hormone-dependent advanced prostate cancer - Perachino, Massimo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2013)
INTRODUCTION: Prostate cancer (PC) is a very common tumor among men: in Italy its prevalence in 2006 was 0.9%. Androgen deprivation therapy is a way to treat hormone-responsive PC by decreasing testosterone levels. GnRH-analogues, including GnRH-agonists and GnRH-antagonists, are effective for this purpose. AIM: This article presents a cost-effectiveness analysis based on a semi-Markov model comparing the GnRH-antagonist degarelix and GnRH-agonist leuprolide in the treatment of hormone-dependent advanced prostate cancer from the perspective of the Regional Health Service in Veneto Region (Italy). MATERIALS AND METHODS: Effectiveness data were retrieved by a 12-month phase III non-inferiority clinical trial, comparing degarelix and 7,5 mg leuprolide in 610 patients treated for hormone-dependent prostate cancer. Epidemiological data came from a national database and were referred to Veneto Region. The values of the healthcare resources were calculated using regional and national prices (€ 2012). The model considers 3 exhaustive and mutually exclusive health status: first-line treatment, further-lines treatment and death. It lasts 10 years, with 28 days per cycle. The entry in the model is hypothesized at the age of 70 (the age with most PCs in Veneto Region). Effectiveness endpoints were life years saved and quality-adjusted life years, using 3% social discount rate. The incremental cost per QALY was related to the range of acceptability proposed by the Associazione Italiana di Economia Sanitaria (€ 25,000-40,000). The budget impact was calculated on a 5-year time horizon. Univariate and probabilistic sensitivity analyses were performed on every hypothesis of the model. RESULTS: Degarelix resulted in minor costs if compared to 7.5 mg leuprolide (€ 20,511.64 vs 22,256.49). The cost-driver was chemotherapic care (32.45% degarelix vs 44.30% 7.5 mg leuprolide). Life years saved were the same for both the alternatives (5.58), while QALYs obtained were higher in degarelix vs. 7.5 mg leuprolide (4.41 vs. 4.10). QALY better data probably could results from greater delay to disease progression in castrate resistant phase with degarelix than comparator and also due to superior symptoms relief. Therefore degarelix is dominant compared to the agonist. The probability for degarelix to be cost-effective increases with the increasing of the threshold for incremental QALY, being 69.95%, 93.76%, 95.55%, and 97.42% for threshold values equal to € 0, € 25,000, € 40,000, and € 100,000, respectively. The use of degarelix in Veneto Region instead of 7.5 mg leuprolide would result, after a five-year period, in total savings for the Regional Health Service equal to € 4,783, considering the treatment of 259 patients. CONCLUSIONS: In the treatment of hormone-dependent advanced prostate cancer PC, degarelix is thought to be an economically rational investment of resources for the Regional Health Service of Veneto Region because it’s dominant, in term of cost-effectiveness, to the comparator (agonist) thanks to superior QALY and reduced costs.